INVESTIGASI PENYEBAB GENANGAN BANJIR DI KAWASAN AEROTROPOLIS YOGYAKARTA INTERNATIONAL AIRPORT - Shofwatul Fadilah; Istiarto; Djoko Legono (TEKNISIA, 2023)
The Yogyakarta International Airport (YIA) Aerotropolis area, Kulon Progo, is in an area prone to flooding. Some areas are flooded during the rainy season, including the Carik drainage channel that flows the discharge into the Bogowonto River on the west side and the Serang River on the side of east. This paper describes the results of the investigation of flood inundation that occurred in the drainage system of the YIA Aerotropolis area to determine the causes of flood inundation. The data were collected from literature studies, observations, interviews, and documentation at the study locations. Interviews were conducted using a questionnaire to the community around the drainage system of the study location. The data is then processed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with SMART PLS 3.0 software. The investigation results show the inundation of floods in the Aerotropolis area of Yogyakarta International Airport caused by flood discharge from upstream, the influence of the Serang and Bogowonto Rivers, and the condition of the canals and buildings in the drainage system. Based on the Structural Equation Modeling-Partial Least Square (SEM-PLS) test results using SMART PLS 3.0, there is a positive effect from channel flow conditions and surface runoff to the flood inundation in the YIA Aerotropolis area. Based on the bootstrapping test, the t-test value was more than 1.96, while the p-test value showed a value of less than 0.05 for each factor causing flood inundation in the YIA Aerotropolis area.